Erratum: A whole-of-population study of the prevalence and patterns of criminal offending in people with schizophrenia and other mental illness (Psychological Medicine (2013) 43(09) (1869–1880) (10.1017/S0033291712002887)) - Morgan, V.; Morgan, F.; Valuri, G.; Ferrante, Anna; Castle, D.; Jablensky, A. (Cambridge University Press, 2013)
The publisher apologizes for errors introduced into the key of Figure 2 in this article (Morgan et al. 2012). The lines for ‘Schizophrenia’ and ‘No psychiatric illness’ were accidentally transposed. The correct Figure 2 is given below. © 2013, Cambridge University Press. All rights reserved.